Vernacular Architecture - Mumbai Archive Project Team (Jio Institute, 2024)
The vernacular architecture in the village primarily comprised single-story dwellings constructed from locally available materials such as bamboo, mud, wood, thatch, plaster, brick, and cow dung. Traditionally, these houses were built on raised plinths to protect them from flooding in the monsoon.